Pentatrichomonas hominis induces extracellular traps formation of macrophages via the TLR2/NADPH/PAD4 pathway - Zhai, Qi-an; Zhang, Xi-chen; Zhang, Hong-bo; Li, Jian-hua; Gong, Peng-tao; Wang, Xiao-cen; Li, Xin; Zhang, Xu; Zhang, Nan (Parasites & vectors, 2025)
Background Pentatrichomonas hominis ( P. hominis ) is a newly identified pathogenic zoonotic protozoan belonging to the Trichomonadidae family. P. hominis mainly parasitizes the cecum and colon of humans and other mammals, and it can cause diarrhea. Recently, macrophage extracellular traps (METs) have been shown to play an important role in resistance to parasitic infections. However, it remains unclear whether the release of METs by macrophages contributes to P. hominis resistance, and the underlying mechanism of this association has yet to be elucidated. Methods Scanning electron microscopy (SEM) and immunofluorescence staining were used to determine whether P. hominis induced the formation of METs in mouse peritoneal macrophages to capture and immobilize the parasite as well as the components of METs, including the DNA backbone, myeloperoxidase (MPO), and histone H3. Reactive oxygen species (ROS) and signaling pathway inhibitor assays revealed that the mechanism of P. hominis -induced MET formation was dependent on nicotinamide adenine dinucleotide phosphate hydrogen (NADPH) oxidase activation, store-operated calcium entry (SOCE),, and peptidyl arginine deiminase 4 (PAD4) activation. The toll-like receptors 2 (TLR2), extracellular regulated protein kinase 1/2 (ERK1/2) and p38 MAPK signaling pathway were also involved in this process. Trypan blue staining revealed a gradual decrease in the survival rate of P. hominis as the coculture time increased. Trypan blue staining also revealed an increase in the proportion of macrophages. Results The results of this study indicate that P. hominis can induce the release of METs via the TLR2/NADPH/PAD4 pathways and that METs have a trapping and killing effect on P. hominis . Conclusions This was the first study to reveal that PAD4 and TLR2 were found to be involved in the development of parasite-induced METs, thus providing guidance for further research on the mechanisms of host innate immunity against parasitic infection. Graphical Abstract